THE MONETARY POLICY OF THE EUROPEAN CENTRAL BANK IN THE PERIOD OF SOVEREIGN DEBT CRISIS - Andriuškevičiūtė, Deimantė; Balčiūnas, Norbertas (Ekonomika, 2013)
Abstract. The European Central Bank was forced to start using non-standard measures in order to manage the situation determined by the global financial and sovereign debt crisis, namely to sort out liquidity problems and expand credit supply. The European Central Bank is criticized for applying non-standard tools because of increase in inflation risk. However, the analysis shows that the inflation could be managed by the absorption of liquidity surplus. However, there is a negative side of using non-standard measures, such as a significant increase in the credit risk, which arises due to having government bonds in the balance sheet of the European Central Bank. In addition, this indicates that the European Central Bank indirectly finances governments. Key words: monetary policy, inflation, sovereign debt crisis, credit risk, quantitative easing